Prospective changes in Australia’s security strategy in the South Pacific - Yarmoshuk, Karina I. (Journal of the Belarusian State University. International Relations, 2023)
This study, which focuses on regional political relations and security, presents possible future changes in Australia’s security strategy in the South Pacific region. The goal is to develop a short-term forecast for Australia’s security policy in the South Pacific. Eight predictive assumptions are proposed, with a causal explanation for each. The study contributes to research by describing the presumptions driving Australia’s strategic security measures in the South Pacific in the decade beginning from 2022, as obtained from an examination of Russian and English language materials and historiography. The findings can help shape future research on the South Pacific and, more broadly, on regional security.
Keywords: South Pacific region; military-political cooperation; infrastructure projects; Belt and Road initiative; Blue Dots network; regional leadership